2005
DOI: 10.3748/wjg.v11.i10.1426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between combination therapy of percutaneous ethanol injection and radiofrequency ablation and radiofrequency ablation alone for patients with hepatocellular carcinoma

Abstract: These results suggest that, compared to RFA alone, PEI-RFA enables to induce comparable coagulated necrosis with smaller energy requirement, and that PEI-RFA is likely to be less invasive than RFA alone irrespective of inducing enhanced coagulated necrosis. Thus, simple prior injection of ethanol may make RFA treatment more effective and less invasive for the treatment of patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
2
37
0
1
Order By: Relevance
“…As one of the optional combination therapies, we have shown that injection of ethanol prior to RFA (PEI-RFA) markedly enlarged the induced coagulated necrosis in human (20,21) and in bovine livers (33). Furthermore, we showed that PEI-RFA is a less invasive treatment modality from the standpoint of energy requirement for inducing coagulated necrosis (24). In the present study, we thoracoscopically applied this combination therapy for the treatment of HCC located immediately under the diaphragm.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As one of the optional combination therapies, we have shown that injection of ethanol prior to RFA (PEI-RFA) markedly enlarged the induced coagulated necrosis in human (20,21) and in bovine livers (33). Furthermore, we showed that PEI-RFA is a less invasive treatment modality from the standpoint of energy requirement for inducing coagulated necrosis (24). In the present study, we thoracoscopically applied this combination therapy for the treatment of HCC located immediately under the diaphragm.…”
Section: Discussionmentioning
confidence: 81%
“…However, several limitations of RFA have been pointed out, such as limited coagulated necrosis and relatively frequent local tumor recurrences. To overcome these weaknesses, we have developed a novel combination therapy of percutaneous ethanol injection (PEI) and RFA and showed that combined use of PEI prior to RFA was able to enhance the therapeutic effect with smaller energy requirement compared with RFA alone (20)(21)(22)(23)(24). Although PEI-RFA was shown to enlarge the area of coagulated necrosis, there are cases with HCC that are difficult to treat with a percutaneous approach due to the location of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that the amount of ethanol was positively correlated with the volume of coagulated necrosis in patients treated with P-EI-RFA using an RFA instrument equipped with a straight electrode (Cool-tip RF system) [19] . In the present study, the relationship between the amount of ethanol or applied energy and the volume of induced coagulated necrosis were evaluated in patients treated with EI-RFA under general anesthesia.…”
Section: Relationship Between the Amount Of Ethanol Applied Energy mentioning
confidence: 99%
“…After visualizing the tumor by US, an RFA electrode was inserted into the tumor through the channel along the End-fire laparoscopic probe. A 21-gauge PEI needle was inserted and pure ethanol or lipiodol containing ethanol was injected [19] .…”
Section: Thoracoscopic Time-lag Ei-rfa (T-ei-rfa)mentioning
confidence: 99%
See 1 more Smart Citation